Occurrence of gold in hydrothermal pyrite, western Taupo Volcanic Zone, New Zealand. Issue 3 (2nd July 2016) - Zhang, Youjun; Kusky, Timothy; Wang, Lu; Li, Jianwei; Feng, Peng; Huang, Yang; Giddens, Roy
Abstract : The Taupo Volcanic Zone (TVZ) on the North Island of New Zealand is located above the subducting Pacific slab and hosts hydrothermal systems related to subduction, arc magmatism and crustal extension. In these systems, gold is transported primarily as sulphide complexes, with gold being deposited in response to boiling and mixing of the deep geothermal fluids. Conglomerate cobbles and hydrothermal fumaroles from the upper Retaruke River in the western TVZ are mineralised deposits that have been eroded from the nearby Miocene alluvial sedimentary plateau. Abundant gold-bearing pyrite was precipitated in the conglomerates and fumaroles by late hydrothermal process, primarily occurring as veinlets, disseminations and fine-grained aggregates which consists discrete euhedral microcrystals. Scanning electron microscopy combined with X-ray energy disperses spectroscopy shows that pyrites are commendably affected by late hydrothermal fluids, possibly by the carbonate fluid. Electron probe microanalysis revealed that the pyrite contains 20–120 ppm Au (averaging 60 ppm). Wavelength dispersive spectral elemental mapping suggests that gold is distributed uniformly in pyrite, indicating structurally bound gold (solid solution) in pyrite. Gold mineralisation recognised in the conglomerates and fumaroles demonstrates that the upper Retaruke River is a promising target for future gold exploration.